Theory of surface acoustic wave reversing multistrip coupler - DANICKI, E. (Archives of Acoustics, 1994)
A reversing, multistrip coupler device is presented that can find numerous applications in SAW devices. Fundamental theory and first experimental results are presented on an application of rmsc in SAW resonator.